Case report of an enigmatic childhood hematomalignancy - M Geetha; B Kiran; Madhusmitha Jena; V Rangaiah; Nikhila R Reddy; T Himabindu (Wolters Kluwer Medknow Publications, 2019)
Juvenile Myelomonocytic Leukemia (JMML) is a rare leukemia of children we are still in the process of unraveling presenting a frustrating and dismal picture. We diagnosed JMML in 4 year old boy evaluated for progressive abdominal distension with massive splenomegaly.